Capital structure and firm performance of non-financial listed companies: Cross-sector empirical evidences from Vietnam - Thanh Hieu Nguyen; Huu Anh Nguyen (Accounting, 2020)
This paper examines the relationship between capital structure and profitability of non-financial companies listed on Vietnam's stock market. The panel data is extracted from financial statements of 488 listed companies between 2013 and 2018. Capital structure discussed is represented by the ratios of short-term liabilities, long-term liabilities and total liabilities to total assets, and profitability is measured by Return on Equity (ROE), Return on Assets (ROA) and Earnings per share (EPS). Firm size, growth rate, liquidity, ratio of fixed assets to total assets are control variables in the study. The Generalized Least Square (GLS) is applied to different models, including ROE, ROA and EPS Model, and tests of autocorrelation, multicollinearity and heteroskedasticity are run to confirm the relationship between capital structure and business performance. The results show that the capital structure of Vietnamese listed non-financial companies is negatively related to their performance. Taking industrial product sectors as the preference sectors, the results show that pharmaceutical and medical, the consumer goods and the public utility industries had a higher relationship between capital structure and firm’s performance (via ROE, ROA, EPS) than industrial product sectors. These evidences are useful new insights to investors, business managers and governmental authorities.